The Relationship between Korea’s Direct Investment and Export on the Economic Growth of Laos - PHOMMANY, Sombath; SIPHADA, Vatthanaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The goal of this study is to demonstrate the connection between three factors: the GDP growth of Laos, Korean direct investment in Laos, and Lao exports to Korea. The research approach is based on secondary data from many sources. The variables were recorded as annual data from 2002 to 2024, and every association was analyzed using the vector autoregression model (VAR). As a result, 23 observations were included in this estimation. The results of the stationary property test showed that only two variables were determined to be stationary at 1st difference level by the ADF test, whereas the PP test found all variables to be stationary at level. However, it was permissible to identify this distinction. The VAR model results, which show the long-term relationship between GDP growth, exports, and FDI, identified a significant return to equilibrium, as represented by the equation coefficient. After completing an experiment with the lag (lagged value) in the VAR Model program, it was determined that a lag level of 2 is the right one. Each variable in this study is equal to t-2 since the GDP calculation produces that value. The vector autoregressive results showed a long-term relationship between GDP growth, exports and FDI. GDP will rise 0.071 and 0.032 units if exports increase by one unit, while GDP will increase 0.1725 and 0.1560 if investment in Laos decline by one unit. Form an impulse reaction it is discovered that FDI fluctuates slowly; it will increase by 1 unit, causing the GDP to decline sharply in the second year, then gradually increase to a positive number in the fifth year, and eventually reach the equilibrium point in the ninth year. In the first 2, 3, and 4 years of an increase in exports of 1 unit, the GDP growth rate will increase significantly.